تأثير الأزمات على قطاع السياحة مؤشرات من سورية ودول الجوار - شريقي طرفة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The goal of this paper is study crises that affect tourism sector and to clarify its concept. The research explains major issues related to tourism crisis. And classifies tourism crises temporally. The researcher then reviews tourism crises according to their nature, and classifies them into five major groups. The paper also studies the methods available for measuring the intensity of these crises. The paper additionally tries to demonstrate the impact of the crisis engulfing Syria and its neighbors on tourism economy. The research studies three indicators of a selected group of countries, these indicators are: Tourism arrivals, Tourism receipts, and the role of tourism in the national economy of the effected countries. The papers reaches conclusions about the relation between the nature and intensity of the crisis and its impact on the economy. يهدف هذا البحث إلى دراسة الأزمات التي تؤثر على قطاع السياحة وتوضيح مفهومها. حيث يعرض الباحث للمفاهيم الأساسية المتعلقة بالأزمة السياحية، ويبين أنواع الأزمات السياحية وفقاً لبعدها الزمنـي. ويستعرض البحث أنواع الأزمات السياحية وفقاً لطبيعتها حيث يقسمها إلى خمس مجموعات رئيسية. كما يوضح البحث الطرق المتبعة لقياس مستوى وشدة هذه الأزمات. يحاول البحث، بالإضافة إلى ما سبق، أن يوضح أثر الأزمة التي تمر بها سورية ودول الجوار على اقتصاد السياحة فيها. ويدرس من خلال مجموعة مختارة من الدول، أثر الأزمة على عدد الوافدين من السياح، وإيرادات السياحة، ودور السياحة في الاقتصاد الوطني في الدولة المتضررة. ويتوصل إلى وجود علاقة بين شدة وطبيعة الأزمة وبين الآثار على الاقتصاد السياحي في دولة المقصد المتضرر.